Design of an anti-reflective coating for a specific polarization pattern based on the concept of modified optical permittivity (Journal of the College of Basic Education, 2022)
The research includes a study of designing an anti-reflective coating with different angles of incidence and a specific polarization pattern based on the principle of modified optical permittivity. Deposited based on the concept of modified optical permittivity as well as the use of analytical methods (optical thickness fit) to achieve the requirement of zero reflectivity.